Ion microprobe (SHRIMP) dates complex granulite from Santa Catarina, southern Brazil - HARTMANN,LÉO A. (2000)
Complex polymetamorphic granulites have been dated in the Santa Catarina granulite complex of southern Brazil through SHRIMP study of zircon. This complex is dominated by intermediate-acid plutonic rocks and contains small volumes of mafic and ultramafic rocks, and minor quartzite and banded iron formation. Porphyroblasts of orthopyroxene, clinopyroxene and plagioclase in mafic and acid rocks are interpreted as magmatic remnants in a volumetrically dominant granoblastic aggregate (M1) of the same minerals and hornblende. Hornblende formed during a later M2 metamorphic event constitutes rims around pyroxene, but the hornblende is also rimmed by granoblastic simplectites of orthopyroxene, clinopyroxene, hornblende and plagioclase in a second granulite facies event (M3). Chlorite and epidote occur in shear zones (M4). This granulite terrain is part of a Neoproterozoic craton, because it was little affected by the Brasiliano Cycle. The two granulite-facies events (M1 and M3) are dated by U/Pb zircon SHRIMP at about 2.68 and 2.17 Ga, while the magmatic protoliths formed at about 2.72 Ga. The amphibolite facies event (M2) probably occurred close to the 2.17 Ga granulitic metamorphism.